Mid-infrared dielectric laser acceleration in a silicon dual pillar structure - Brückner, Leon; Chlouba, Tomas; Morimoto, Yuya; Schönenberger, Norbert; Shibuya, Tatsunori; Siefke, Thomas; Zeitner, Uwe D.; Hommelhoff, Peter (Optics Express, 2024)
Dielectric laser accelerators use near-infrared laser pulses to accelerate electrons at dielectric structures. Driving these devices with mid-infrared light should result in relaxed requirements on the electron beam, easier fabrication, higher damage threshold, and thus higher acceleration gradients. In this paper, we demonstrate dielectric laser acceleration of electrons driven with 10 µm light in a silicon dual pillar structure. We observe the acceleration of 27 keV electrons by 1.4 keV, corresponding to a 93 MeV/m acceleration gradient. The damage threshold of the structures of 3.3 ± 0.6 GV/m peak field is significantly higher than for near-infrared accelerators. The dual pillar acceleration structure itself even survived 5.2 ± 0.9 GV/m, the highest field strength we could achieve with the current system. This together with the larger structure acceptance bodes well for future dielectric laser accelerators driven with mid-infrared light.
CRIS-Team Scopus Importer:2024-08-09